2011
DOI: 10.1097/jnr.0b013e31821aa155
|View full text |Cite
|
Sign up to set email alerts
|

Preceptors' Experiences Training New Graduate Nurses

Abstract: Being in the role of both a preceptor and nurse was perceived as a challenge by participants because of heavy workloads and fears of failure. Thus, reducing the preceptor's patient care responsibilities while educating new nurses should be a priority. This study also found cultivating a positive work climate as crucial to support preceptors and new nurses so that preceptors do not feel alienated or overly stressed. A workshop is a useful strategy to introduce preceptors and new nurses to standardized training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 15 publications
2
25
0
1
Order By: Relevance
“…Overall, participants in this study perceived the role of preceptorship as being challenging, leading to a great deal of stress. These adverse experiences appear to be common among the preceptors across different settings and countries (Chen et al, 2011;Liu et al, 2010;Panzavecchia and Pearce, 2014;Richards and Bowles, 2012). The preceptors, in the current study, were appointed to the role with no consultation or prior notice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, participants in this study perceived the role of preceptorship as being challenging, leading to a great deal of stress. These adverse experiences appear to be common among the preceptors across different settings and countries (Chen et al, 2011;Liu et al, 2010;Panzavecchia and Pearce, 2014;Richards and Bowles, 2012). The preceptors, in the current study, were appointed to the role with no consultation or prior notice.…”
Section: Discussionmentioning
confidence: 99%
“…Also, if related to the mission and goals of the nursing unit, this role can help with the successful implementation of changes within the unit (Moore, 2008). The program has been found successful in retaining new nurses in the profession (Chen et al, 2011;Goss, 2015), and provided personal and professional growth opportunities for the preceptors (Chen et al, 2011;Muir et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[32] Research has been recommended to measure long term outcomes, including the long-term cost reduction related to preceptorship programs to determine the effectiveness of these programs in turnover rate of new nurses. [27] Similarly, Sandau et al [29] suggested that there is a need for further studies on retention of new nurses after implementing preceptorship programs.…”
Section: Retention Of New Nurses and Cost Savingmentioning
confidence: 99%
“…However, these authors also found that if these preceptors had not received any support or caring, job satisfaction of preceptees and preceptors may have decreased and intention to leave health care settings may have increased. [27] Preceptors also require support from their hospital units and organizations to deal with workplace demands. Ongoing support of preceptors could be provided by their units through decreasing clinical work load, scheduling preceptors and preceptees on the same shift, and establishing networks with other units to support preceptors' activities.…”
Section: Organizational Supportmentioning
confidence: 99%
See 1 more Smart Citation